On a Nonlocal Boundary Value Problem of a State-Dependent Differential Equation - Ahmed El-Sayed (MDPI AG, 2021)
In this paper, the existence of absolutely continuous solutions and some properties will be studied for a nonlocal boundary value problem of a state-dependent differential equation. The infinite-point boundary condition and the Riemann–Stieltjes integral condition will also be considered. Some examples will be provided to illustrate our results.